Discharge readiness and its associated factors among first-time mothers undergoing cesarean section in China - Mingfei Ran; Praneed Songwathana; Jintana Damkliang (Belitung Raya Foundation, Indonesia, 2022)
Background: Helping first-time mothers who have just undergone cesarean section and transitioning from hospital to home with their infant is a complex process. Therefore, understanding what contributes to discharge readiness is necessary. Objective: This study aimed to determine discharge readiness level and its associated factors among first-time mothers who have undergone cesarean section. Methods: A descriptive cross-sectional study was conducted among 233 first-time mothers who had undergone cesarean sections selected using quota sampling from the two largest referral centers in China. Data were collected from March to June 2021 using a demographic characteristics form, Readiness for Hospital Discharge Scale-New Mother Form (RHDS-NMF), and Quality Discharge Teaching Scale-New Mother Form (QDTS-NMF). Descriptive and inferential statistics were used for data analysis. Results: The discharge readiness of the respondents was at a moderate level. Age (r = -0.129, p = 0.049) and complications after cesarean section (r = -0.136, p = 0.038) had a negative correlation with discharge readiness. In contrast, the subscales of QDTS-NMF, particularly the content (r = 0.519, p = 0.000) and delivery (r = 0.643, p = 0.000), had a positive correlation with discharge readiness. Conclusion: The findings enable nurses, midwives, and other healthcare professionals to understand discharge readiness and its related factors among first-time mothers undergoing cesarean section. It is also suggested that the quality of discharge teaching with a comprehensive assessment of first-time mothers preparing for discharge from the hospital and following the guideline to prevent post-cesarean section complications should be reinforced.